2020
DOI: 10.31067/0.2020.246
|View full text |Cite
|
Sign up to set email alerts
|

Gebelik Döneminde Çiftler Arası Uyum ve Prenatal Bağlanma Arasındaki İlişki

Abstract: Amaç: Çalışmamızda, gebelik döneminde çiftler arası uyum ve prenatal bağlanma arasındaki ilişkiyi incelemek amaçlanmıştır. Hastalar ve Yöntemler: Kesitsel tipteki bu çalışma Ocak-Mart 2018 tarihleri arasında bir üniversite hastanesinin kadın hastalıkları-doğum polikliniğine başvuran n=195 gebe üzerinde yürütülmüştür. Araştırma verileri, "Anket Formu'' , "Çiftler Uyum Ölçeği (ÇUÖ)" ve "Prenatal Bağlanma Envanteri (PBE)'' kullanılarak toplanmıştır. Bulgular: Gebelerin yaş ortalaması 29.5±6.3, eşlerinin yaş ortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 17 publications
(20 reference statements)
3
16
0
11
Order By: Relevance
“…[20] In the study of Küçükkaya et al, the authors found that the prenatal attachment level of those graduated from high school or with higher education levels was significantly higher than those graduated from primary school or with lower education levels. [23] While these two studies are not similar to our study, Özkan et al reported in their study similar to our study that the prenatal attachment level of the pregnant women graduated from primary school was higher than the other pregnant women. [21] The studies conducted show that the educational level affects prenatal attachment differently.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…[20] In the study of Küçükkaya et al, the authors found that the prenatal attachment level of those graduated from high school or with higher education levels was significantly higher than those graduated from primary school or with lower education levels. [23] While these two studies are not similar to our study, Özkan et al reported in their study similar to our study that the prenatal attachment level of the pregnant women graduated from primary school was higher than the other pregnant women. [21] The studies conducted show that the educational level affects prenatal attachment differently.…”
Section: Discussionsupporting
confidence: 55%
“…[22] Küçükkaya et al also found in their study that the prenatal attachment level of those whose incomes are higher than or equal to their expenses were higher than those whose incomes are lower than their expenses. [23] While the results of these two studies are not in parallel with our study, Damato reported similar to our study that the prenatal attachment level of those with low income level was higher. [30] Mental and emotional conditions of a pregnant woman affect the course of pregnancy.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Sağlıklı bir gebelik sürdürmek için çiftler arası uyumun ve prenatal bağlanmanın olması önemlidir. 11 Gebelik döneminde, fetüse bağlanma merkezi roldedir. 12 Ebeveynler ile doğmamış bebekleri arasında kurulan duygusal bağ prenatal bağlanma (doğum öncesi bağlanma) olarak adlandırılmaktadır.…”
Section: Introductionunclassified
“…13 Prenatal bağlanma, anne adayının bebeğini karnında hissettiği andan itibaren sevgiyle bağlanmasıdır. 11 Gebelikte anne adayının bebeğine bağ¬lanmasını etkileyebilecek önemli psikolojik ve fizyolojik değişiklikler meydana gelmektedir. 14 Riskli gebeler, gebeliklerinde yaşadıkları riskler nedeniyle stres ve anksiyete yaşamaktadırlar.…”
Section: Introductionunclassified